ANALISIS PENGARUH MAKRO EKONOMI DALAM NEGERI DAN INDEKS HARGA SAHAM LUAR NEGERI TERHADAP PERGERAKAN INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Indra Galis Panggraito (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2014)
The purpose of this research was to analyze the effect of the inflation rate, the BIrate, foreign exchange rates, the Dow Jones, the Nikkei 225 index and the Hang Sengindex againts movement Jakarta Composite Index. This research was conducted duringthe period January 2009 until December 2013. Data collection techniques used themethod of documentation, literature review and internet search. This research usedmultiple regression model as a means of testing the hypothesis. Population in this studywas the Indonesia Stock Exchange, using purposive sampling as a sampling technique.The results of this research showed that the rate of inflation, the BI rate, the Nikkei 225index and the Hang Seng index had no significant effect on Jakarta Composite Index,while the foreign exchange rates and the Dow Jones index had significant effect onJakarta Composite Index.